2013
DOI: 10.1186/1472-6882-13-342
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility and growth inhibitory response of oral Candida species to Brucea javanica Linn. extract

Abstract: BackgroundCandida species have been associated with the emergence of resistant strains towards selected antifungal agents. Plant products have been used traditionally as alternative medicine to ease candidal infections. The present study was undertaken to investigate the antifungal susceptibility patterns and growth inhibiting effect of Brucea javanica seeds extract against Candida species.MethodsA total of seven Candida strains that includes Candida albicans ATCC14053, Candida dubliniensis ATCCMYA-2975, Candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Thus, the results obtained have shown the potential use of Piper betle extract as antifungal agent and thus significantly contribute to its antifungal development. as well as, the results were in agreement with that obtained by Nordin et al, (2013) who found that the determination PIDG for Brucea javanica extract compared with chlorhexidine. Based on the percentage, Candida glabrata and C. dubliniensis and followed by C. lusitaniae were highly affected by the extract of Brucea javanica which outstrips the chlorhexidine (positive control).…”
supporting
confidence: 91%
“…Thus, the results obtained have shown the potential use of Piper betle extract as antifungal agent and thus significantly contribute to its antifungal development. as well as, the results were in agreement with that obtained by Nordin et al, (2013) who found that the determination PIDG for Brucea javanica extract compared with chlorhexidine. Based on the percentage, Candida glabrata and C. dubliniensis and followed by C. lusitaniae were highly affected by the extract of Brucea javanica which outstrips the chlorhexidine (positive control).…”
supporting
confidence: 91%
“…Earlier findings on antimicrobial activity of seed oil and plant extracts have shown a dose-dependent increase in activity. 26,27 We reported the MIC values of C. albicans and C. krusei only as the former is a common oral pathogen and the latter a highly resistant strain.…”
Section: Discussionmentioning
confidence: 99%
“…One donor was asked to contribute throughout the whole experiment to minimize any variations that may arise because of different subjects. The collected saliva was centrifuged for 30 min at 17,000g and filter-sterilized using sterile 0.2 mm cellulose acetate syringe filter (Sartorius) and stored at À20 C prior to use [12].…”
Section: Collection and Preparation Of Saliva For Biofilmmentioning
confidence: 99%